PERAN PENGEMBANGAN KARIR DAN MOTIVASI SEBAGAI MEDIASI PENGARUH DISIPLIN KERJA TERHADAP KINERJA PEGAWAI - La Ode Muhammad Syafaruddin; Adnan Hakim; La Ode Bahana Adam (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
The objective of this research is to analyze the effect of work discipline on career development, motivation and employees performance. Also, the effect of career development and motivation on the performance. In addition, an examination was conducted to find how mediation of career development and motivation on correlates the work discipline on employees performance.The research population is all 31 employees of the National Unity and Politics Bureau of Wakatobi Regency. The analytical equipment used is Partial Least Square with the Smart PLS apps.The result shows that work discipline has positive and significant effects on career development, employees motivation and performance, whereas career development has no significant effects on employees performance but work motivation has positive and significant effects on employees performance. Another finding shows that career development does not mediate the effect of work discipline on the performance but motivation plays a role in mediation.Keywords: work discipline, work motivation, career development and employees performance